Value foundations of the multiple self and reflexive choice as student's resources in stress resistance and adaptation in multicultural groups - V. G. Gryazeva-Dobshinskaya; E. I. Koltunov; Yu. A. Dmitrieva; E. S. Naboichenko; J. Zhi (Russian State Vocational Pedagogical University, 2023)
Introduction. The present research is dedicated to an urgent problem of investigating the stress experience and adaptation by students studying in a multicultural environment of modern universities. In the course of studying the resources for stress resistance and adaptation, the authors analysed Chinese and Russian students' value priorities and value realisation based on the concept of multiple self. The relevance of the chosen approach is based on the existence of intrapersonal value conflict experienced by students studying in the multicultural university environment and interaction with representatives of other cultures.Aim. The current research aims to conduct cross-cultural analysis of values of the multiple self and the reflective choice of Chinese students in the context of stress experience and adaption to stressfulsituations in a new culture, and students from Russia studying in the environment of multicultural interaction.Methodology and research methods. The authors used a comparative analysis of the significance of values and their realisation among representatives of different cultures in the situation of experiencing stress and adaptation to stressful situations in the multicultural educational environment.Results and scientific novelty. The study allowed the authors to analyse the factors of successful adaptation to a different culture on the sample of Chinese and Russian students studying in the same multicultural environment. The research revealed values specific for students from different culture groups with a high level of adaptation to the multicultural environment of a modern university: health, art, career, power, education for students from China, freedom and friendship for students from Russia. Cultural-specific differences were found in the successful realisation of personal value standards in the field of love (more achievable for the group of Chinese students) and freedom (more achievable for Russian students). Cultural groups with varying degrees of adaptation to the multicultural environment of the university were identified and analysed. The obtained results on specifics of students' adaptation to the multicultural educational environment could be used as the basis for a differential approach to further cross-cultural studies.Practical significance. The analysed specifics of the reflection on the value priorities from different substructures of the multiple self and the established differences in the realisation of personal value standards of students from China and Russia can be used in the consulting practice of cultural adaptation centres.